PENINGKATAN KINERJA PENGURUS PANTI MELALUI IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA YANG EFEKTIF DI PANTI ASUHAN MUHAMMADIYAH GOMBONG - Kalidhamar, Gearintis Lintang; Fadilah, Fikri Nur (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2025)
Human Resource Management is the development and utilization of personnel (employees) for the effective achievement of individual, organizational, community, national and international targets and goals. Development is a process, method or act of developing or the result of developing work. In other words, development is any activity intended to change behavior, behavior consisting of knowledge, skills and attitudes. To ensure the success of this mission, it is important for orphanages to have quality and competent human resources. This research aims to analyze competency-based human resources at the Gombong Muhammadiyah Orphanage. A qualitative approach was used to collect data through in-depth interviews, observation and document analysis. The research results show that the Gombong Muhammadiyah Orphanage has adopted a competency-based approach in their human resource management. Caregiver training and development programs are regularly held to improve the skills and knowledge of caregivers in supporting the development of children living in orphanages. In addition, the use of competency-oriented management performance evaluation methods has increased the efficiency and effectiveness of the organization. Apart from that, this research also identified several challenges faced by the Gombong Muhammadiyah Orphanage in managing competency-based human resources. Lack of funding for training and development, as well as limited access to educational and training resources, are key obstacles that need to be overcome. Nevertheless, the Gombong Muhammadiyah Orphanage has succeeded in overcoming most of these challenges through creativity, collaboration with external partners, and the use of information technology. This study concludes the importance of a competency-based approach in improving the quality of orphanage services. Recommendations include increasing funding for training and development, developing partnerships with education and training institutions, and utilizing information technology to increase access to educational resources. By implementing these recommendations, orphanages can continue to improve the quality of their services and have a positive impact on the development of the children they serve. Keywords: Competence, orphanage, organization